District administrator perspectives of current and ideal approaches to identifying and supporting student social, emotional, and behavioral needs - Chafouleas, Sandra M.; Cintron, Dakota W.; Koslouski, Jessica B.; Briesch, Amy M.; McCoach, D. Betsy; Dineen, Jennifer N. (Frontiers in Education, 2024)
Introduction Leadership support has been identified as a key facilitator to successful implementation of school-based initiatives. School leadership contributions to student academic success and school reform have been documented, but less work has focused on the effects of leadership on school mental health initiatives such as social, emotional, and behavioral (SEB) screening. Few studies have investigated administrator knowledge and support for SEB screening or compared their current and ideal approaches to SEB screening, both of which are important to informing directions for implementation supports. Methods Using a nationally representative sample of U.S. public school districts, we investigated tensions between school district administrators’ (n = 1,330) current and ideal approaches to SEB screening within the current study. We fit binomial and multinomial logistic regression models to determine predictors of positive, negative, or no tensions based on the administrators’ current approach to SEB screening, administrators’ beliefs about the role of schools in student SEB concerns, and district demographics. Results Nearly half of administrators (46.7%) reported using an approach to SEB screening that was not their ideal approach. Higher beliefs scores commonly predicted administrator desire for more proactive approaches, whereas district characteristics yielded varied results. Discussion Results call for targeted next steps, including implementation supports, funding, and knowledge building aligned with administrator and district characteristics.